Salt stress tolerance and stress proteins in pearl millet (Pennisetum glaucum (L.) R. Br.) - R. Johnsi Rani (Journal of Applied Pharmaceutical Science)
Salt stress as a major adverse factor can lower leaf water potential, leading to reduced torgor and some other responses, and ultimately lower crop productivity in arid and semi arid zone. Plant responses to salt stress have much in common. Salt stress reduces the ability of plants to take up water and this quickly causes reductions in growth rate. The initial reduction in shoot growth is probably due to salt effects. If excessive amounts of salt enter into the plant, salt will eventually rise to toxic levels and reduce the photosynthetic leaf area of the plant that cannot sustain growth. In order to understand the processes that give rise to tolerance of salt and to identify the salt stress proteins in the salt stress effect of on plant growth was studied using different salt solutions like Copper sulphate, Cadmium chloride and zinc sulphate with different concentrations like 200µM, 150µM, 100µM.
Keywords: CuSO4.5H2O-Copper sulphate, CdCl2.H2O-Cadmium chloride, ZnSO4.7H2O-Zinc sulphate, growth, salt tolerance, pearl millet.